2022
DOI: 10.3390/jcm11247407
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of Femoral Shaft Pseudarthrosis, Case Series and Medico-Legal Implications

Abstract: Pseudarthrosis (PSA) is a possible complication of femoral shaft fracture treatment. It is often associated with reduced bone quality and can, therefore, adversely affect quality of life. Its treatment poses a major challenge for orthopaedic surgeons. Several authors have set forth different surgical approaches for the treatment of pseudarthrosis, such as internal fixation with plate and screws, replacement of an intramedullary nail or prosthetic replacement. In cases associated with bone loss, osteopenia, or … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 41 publications
0
8
0
Order By: Relevance
“…showed that unstable fractures according to AO/OTA were accompanied by early device failure that required reoperation and mortality after trochanteric hip fractures. It should also be considered that the surgical method employed and its proper execution affects the subsequent outcomes 55 . Several studies comparing the gamma nail and DHS have indicated that DHS seems to be a better method for treatment of trochanteric fractures 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…showed that unstable fractures according to AO/OTA were accompanied by early device failure that required reoperation and mortality after trochanteric hip fractures. It should also be considered that the surgical method employed and its proper execution affects the subsequent outcomes 55 . Several studies comparing the gamma nail and DHS have indicated that DHS seems to be a better method for treatment of trochanteric fractures 56 , 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Pseudarthrosis in femoral fractures is one of the most difficult-to-treat complications, occurring in less than 1% of operated patients [1]. Nonunion (NU) is a condition characterized by incomplete healing within 9 months of injury or no signs of bone callus formation on subsequent radiographs within 3 months; nonunion can be classified as hypertro-phic NUs.…”
Section: Introductionmentioning
confidence: 99%
“…Osteosynthesis, bone reduction, bone grafting, and fixation were not considered as solutions because of previous failures and the possibility of large avascular distal fragments of the humeral shaft that made bone integration unlikely. [5][6][7][8]. The patient underwent general anesthesia, in the supine position, with her left arm crossing her body.…”
mentioning
confidence: 99%
“…The deep layers of the triceps muscle were sutured with non-absorbable suture and then the deep layer of the skin and the skin, in a multilayered fashion (f). [5][6][7][8]. The patient underwent general anesthesia, in the supine position, with her left arm crossing her body.…”
mentioning
confidence: 99%
See 1 more Smart Citation